ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT SUKU BUNGA DEPOSITO BANK UMUM DI INDONESIA TAHUN 2010-2014 - Dewi, Selvia Helda; Haryanto, A. Mulyo (Diponegoro Journal of Management, 2015)
The frequently change of banking situation causing the fluctuation of commercial bank’s time deposit interest rate in Indonesia. The purpose of this study is to analyze the effects of Inflation, Capital Adequacy Ratio (CAR), Return On Asset (ROA,) and Loan to Deposit Ratio (LDR) toward Time Deposit Interest Rate of Commercial Bank in Indonesia. The interest rate was showed how much return will be the number of fund has believed by investor or customer for the concerned bank. So,important for the banks to will be analyzed the factors to determined interest rate targeted match with condition of banking and state of economy.Population of this study is all of commercial bank in indonesia. There are 119 bank that were included. The sample determining method to be used is census method, where the number of sample is equal to the number of population. The data in this study is secondary data that is inflation rate and commercial bank financial performance on 2010 – 2014 obtained from Indonesian Monetary Economic Statistics (SEKI) and Indonesian Banking Statistics (SPI) that had been published by Bank Indonesia. Analysis technique used is analyzed multiple linear regression and the hypothesis testing with use F test and t test. Others also done a classic assumption test covering normality test, multicolinierity test, heteroscedastisity test and autocorrelation test. Conclusion from this research describe that statistical result of Inflation variable show positive and doesn’t have significant influence towards Time Deposit interest determination, CAR variable show positive and doesn’t have significant influence towards Time Deposit interest determination, ROA variable show negative and doesn’t have significant influance towards on Time Deposit interest determination, and, LDR variable show positive and significant influence towards Time Deposit interest determination. Adjusted R2 value on this research is 0,350, this mean that 35% of interest variable could be explained by independent variables Inflation, CAR, ROA, and LDR and 65% remnant of these explained by variables outside not listed in the formula.